Spotted hyaenas switch their foraging strategy as a response to changes in intraguild interactions with lions. (8th September 2015) - Périquet, S.; Valeix, M.; Claypole, J.; Drouet‐Hoguet, N.; Salnicki, J.; Mudimba, S.; Revilla, E.; Fritz, H.
Abstract: Large carnivores are keystone species and their foraging strategies may be a determinant in the functioning of communities and ecosystems. The plastic foraging behaviour of carnivores is likely to be influenced by a suite of factors. Here, we studied spotted hyaena diet during two contrasting periods in terms of lion population abundance to investigate the changes in spotted hyaena foraging strategies in response to changes in expected intraguild interactions in Hwange National Park, Zimbabwe. The analysis of hyaena scats and feeding sites of GPS‐tracked individuals revealed that during the period of high lion abundance, spotted hyaena consumption and preference for very large prey (elephant and giraffe) increased, while that of large (buffalo) and medium‐sized prey (zebra, wildebeest and kudu) decreased, despite an increase in spotted hyaena foraging group size. These results suggest a shift from active predation to scavenging as the potential risk of kleptoparasitism by lions and intraguild competition increased. However, the likely increase of lion predation on very large prey due to the increased proportion of adult males in the lion population could also result in intraguild facilitation by providing spotted hyaenas with additional food sources and thus promote coexistence between these species. Our findings suggest that changes in the numerical abundance of competing species can affect their diet and prey preference, which could ultimately increase the intensity of competition (and facilitation) between carnivores and may thus impact prey populations and possibly ecosystem functioning.